1988
DOI: 10.1055/s-2007-1010936
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary NaCl Supplementation on Bone Synthesis of Hydroxyproline, Urinary Hydroxyproline Excretion and Bone45Ca Uptake in the Rat

Abstract: High sodium chloride intakes are regarded as a risk factor for osteoporosis because they increase the obligatory urinary calcium loss and stimulate parathyroid activity. Sodium chloride loads induce osteopenia in the rat. The effect could be due to a decrease in bone formation or a rise in bone resorption. Two experiments were undertaken to study the effects of dietary NaCl supplementation on 3H-hydroxyproline synthesis and 45Ca uptake in femoral bone. Salt-treated rats excreted 1.7 times more total urinary hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 7 publications
3
8
0
Order By: Relevance
“…Therefore, in spite of the hypercalciuria and increased rate of bone resorption in saltsupplemented rats, their bone mass, when adjusted for body weight, was unaffected. This is in agreement with the findings of other studies in rats that found that salt supplementation (80 g/kg diet) for 10 d-8 weeks had no effect on bone mass despite the presence of hypercalciuria and increased bone resorption, as measured by urinary hydroxyproline (Goulding & Gold, 1988;Chan et al 1993). Thus, it may be that, as suggested by Goulding & Gold (1988), the duration of the present study was too short to elicit significant osteopenia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, in spite of the hypercalciuria and increased rate of bone resorption in saltsupplemented rats, their bone mass, when adjusted for body weight, was unaffected. This is in agreement with the findings of other studies in rats that found that salt supplementation (80 g/kg diet) for 10 d-8 weeks had no effect on bone mass despite the presence of hypercalciuria and increased bone resorption, as measured by urinary hydroxyproline (Goulding & Gold, 1988;Chan et al 1993). Thus, it may be that, as suggested by Goulding & Gold (1988), the duration of the present study was too short to elicit significant osteopenia.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with the findings of other studies in rats that found that salt supplementation (80 g/kg diet) for 10 d-8 weeks had no effect on bone mass despite the presence of hypercalciuria and increased bone resorption, as measured by urinary hydroxyproline (Goulding & Gold, 1988;Chan et al 1993). Thus, it may be that, as suggested by Goulding & Gold (1988), the duration of the present study was too short to elicit significant osteopenia. There is, for example, considerable evidence that salt supplementation (80 g/kg diet) for longer periods (2-4 months) reduces bone mass and Ca content in young and adult rats consuming diets either deficient (Goulding & Campbell, 1982Goulding & Gold, 1986;Chan et al 1993) or adequate (Goulding & Campbell, 1984;Chan et al 1993;Chan & Swaminathan, 1994, 1998 in Ca, although some studies have failed to show this (Goulding, 1980).…”
Section: Discussionsupporting
confidence: 92%
“…A reduced femoral Ca level, but not Mg or P levels, arising from an increased rate of bone resorption has also been noted in a recent study in which young growing rats were fed a high-salt diet (Creedon & Cashman, 2000). It may be that, as suggested by Goulding & Gold (1988), the duration of the present study was too short to elicit significant osteopenia. Several studies have shown that bone Ca content (Thomas et al 1988, 1991Persson et al 1993Takeda et al 1993;Peterson et al 1995), bone strength (Thomas et al 1988(Thomas et al , 1991 and bone density (Persson et al 1993;Talbott et al 1998) in young growing rats were reduced by dietary Ca restriction (i.e.…”
Section: Discussionsupporting
confidence: 63%
“…This has been demonstrated in studies examining the release of 45Ca from labelled skeletons (Goulding & Gold, 1986) and the uptake of [3H]hydroxyproline and 45Ca into bone (Goulding & Gold, 1988).…”
Section: S O D I U M -C a L C I U M W I T H Reference To Osteoporosismentioning
confidence: 83%
“…Goulding & Gold (1988) suggested that such increases in urinary hydroxyproline during salt supplementation were mediated by parathyroid hormone (PTH), since PTH is the major determinant of bone resorption rate. This is supported by the finding that parathyroidectomy abolishes the ability of salt to elevate urinary hydroxyproline (Goulding, 1980 6).…”
Section: S O D I U M -C a L C I U M W I T H Reference To Osteoporosismentioning
confidence: 99%